Pietrele, Rumänien. Măgura Gorgana. Ein kupferzeitlicher Siedlungshügel. Die Arbeiten der Jahre 2019 und 2021 - Aquaro, Antonella; Beutler, Katrin; Boroffka, Rodica; Hansen, Svend; Karaucak, Mehmet; Martin, Janine; Scheele, Konstantin; Toderaş Meda (e-Forschungsberichte des DAI, 2022)
During the ongoing archaeological work in Pietrele, Măgura Gorgana (jud. Giurgiu) in Romania, the lower layers of the Copper Age settlement mound were reached during the campaigns of the last years. The recorded features belong to the earliest occupation phase and represent the oldest remains of the settlement. Reaching these layers now makes it possible to record the development of the settlement without gaps and also to comprehensively assess the relationship between the tell settlement itself and the surrounding flat settlement. The integration of scientific studies on the reconstruction of the environment as well as archaeobotanical analyses of material from different areas of the settlement also provide information on the appearance of the landscape and shed light on the interactions between humans and the environment in the 5th millennium BCE.